ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN DEBU KAYU PADA PEKERJA DI INDUSTRI MEBEL CV. CITRA JEPARA KABUPATEN SEMARANG - Indriyani, Dian; Darundiati, Yusniar Hanani; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat, 2017)
CV. Citra Jepara is a company that processes wood into furniture’s product with hectic activity production so it causes indoor air pollution i.e wood dust. Wood dust causes bad impact on health such as respiratory disorder, skin irritation even lung cancer. The purpose of this research was to assess the environmental health risks of wood dust exposure on sanding unit among workers. Sanding unit was chosen because it was the highest dust concentration level in production unit. Research design was using cross sectional with analysis of environmental health risk approach (EHRA). Subject’s population were 30 sanding unit workers and object’s population was the air in sanding unit workplace. While the subject’s samples were 30 sanding unit workers (using total sampling method) the object’s sample was the air in sanding unit workplace with 2 sampling points. Data was analyzed using EHRA stages which were danger identification, respond dose analysis, exposure analysis, and risk characteristics. Result of this research showed that the average of measurement result of total dust concentration in sanding unit was 21,5 mg/m3. Mean weight of worker was 56 kg, mean exposure period was 11 hours, mean exposure frequency was 298 days and mean exposure duration was 6 years. It can be concluded that total dust concentration in sanding unit was above the specified quality standard and mean real time exposure of non carsinogenic and carsinogenic effect was classified as safe. However, life time exposure of non carsinogenic and carsinogenic effect was above 1 and classified as risky. Estimated calculation of real time exposure risk showed that workers would be at risk of non cancer in 30 years ahead. Workers would be at risk of cancer in 25 years ahead.